Andricus forni Pujade-Villar & Nicholls n. sp., a new species of oak gallwasp from China (Hymenoptera: Cynipidae) - Pujade-Villar, Juli; Wang, Yiping; Cuesta-Porta, Víctor; Guo, Rui; Nicholls, James A.; Melika, George (Zootaxa, 2020)
A new sexual form of a gallwasp, Andricus forni Pujade-Villar & Nicholls n. sp., is described from China (Zhejiang province) based on males, females and galls collected on Quercus serrata. Data on the morphology, diagnosis, distribution and biology of the new species are provided. Molecular data are also provided to support this species. A key to Asian Andricus gallwasp species with similar integral leaf galls is presented. Finally we discuss the taxonomic status of Asian Andricus making these integral leaf galls, including uncertainty on the validity of both Andricus quercicola and A. marmoratus.